2013
DOI: 10.1016/j.tpb.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Joint evolution of altruistic cooperation and dispersal in a metapopulation of small local populations

Abstract: We investigate the joint evolution of public goods cooperation and dispersal in a metapopulation model with small local populations. Altruistic cooperation can evolve due to assortment and kin selection, and dispersal can evolve because of demographic stochasticity, catastrophes and kin selection. Metapopulation structures resulting in assortment have been shown to make selection for cooperation possible. But how does dispersal affect cooperation and vice versa, when both are allowed to evolve as continuous tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 62 publications
(99 reference statements)
6
50
0
Order By: Relevance
“…; Hochberg et al. ; Parvinen ). Substantial theoretical work has demonstrated that various factors could allow cooperation to evolve and be maintained despite kin competition, including overlapping generations (Irwin and Taylor ), population structure and environmental context [e.g., range expansion (Datta et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…; Hochberg et al. ; Parvinen ). Substantial theoretical work has demonstrated that various factors could allow cooperation to evolve and be maintained despite kin competition, including overlapping generations (Irwin and Taylor ), population structure and environmental context [e.g., range expansion (Datta et al.…”
mentioning
confidence: 99%
“…However, while group stability among kin provides benefits of kin cooperation, it also increases kin competition, which can negate these benefits (Hamilton and May 1977;Taylor 1992;Queller 1994). This contradiction is even more intriguing given ample empirical evidence of cooperative species performing dispersal movements (Bourke and Franks 1995;O'Riain et al 1996;Sinervo and Clobert 2003), which has led to several theoretical studies showing that cooperation and dispersal can coevolve (Le Galliard et al 2005;Hochberg et al 2008;Parvinen 2013). Substantial theoretical work has demonstrated that various factors could allow cooperation to evolve and be maintained despite kin competition, including overlapping generations (Irwin and Taylor 2000), population structure and environmental context [e.g., range expansion (Datta et al 2013), empty patches (Alizon and Taylor 2008), patch quality (Rodrigues and Gardner 2012); see also (Lion and Baalen 2008)], budding dispersal (Gardner and West 2006;Kümmerli et al 2009), and dispersal-dependent cooperation (El Mouden and Gardner 2008).…”
mentioning
confidence: 99%
“…We hope that our approach will be relevant in a more general setting, and will be useful when identifying and explaining sudden regime changes in multidimensional evolutionary systems. For instance, this framework may be applicable to the joint evolution of dispersal and a wide array of other traits, including co-operation (Le Galliard et al 2005;Parvinen 2013), seed dormancy (Cohen and Levin 1987;Venable and Brown 1988;Olivieri 2001), reproductive effort (Ronce et al 2000;Crowley and McLetchie 2002), sex ratios (Leturque and Rousset 2003), kin recognition (Lehmann and Perrin 2003), inbreeding load (Guillaume and Perrin 2006), mating strategy (Ravigné et al 2006), habitat niche width (Chaianunporn and Hovestadt 2012) and age at death (Dytham and Travis 2006).…”
mentioning
confidence: 99%
“…By contrast, the social polymorphism we report here is underlain by a genetic association among dispersal and social behaviours. Previous models of the co-evolution of unconditional dispersal and cooperation have also found that genetic polymorphism can emerge in asexual haploids [14][15][16] . But these models assume that cooperation has non-linear fitness effects such that polymorphism can arise when cooperation is evolving but the rate of dispersal is fixed.…”
Section: Discussionmentioning
confidence: 92%